Analytic theory for the current-voltage characteristic of a nanowire radial p-i-n diode - Borblik, V.L. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
In this article, the process of current flow in a nanowire radial p-i-n diode has been considered in detail. It has been shown that cylindrical geometry of the structure gives rise to specific asymmetry of the concentration distribution for current carriers injected into the i-layer, which is opposite to the asymmetry that is due to inequality of carriers’ mobilities. This specific asymmetry rises with bringing the i-layer nearer to the nanowire center. Together with that, a decrease of the current density in a “long” p-i-n diode and its increase in a “short” p-i-n diode take place (at a given forward voltage). And variation of radial thickness of the i-layer demonstrates maximums in the current density at the thickness close to the bipolar diffusion length. У роботі детально розглянуто процес струмоперенесення у нанодротовому радіальному p-i-n-діоді. Показано, що циліндрична геометрія структури призводить до специфічної асиметрії розподілу концентрації інжектованих в i-й шар носіїв струму, яка обернена до тієї, що зумовлена нерівністю рухливостей носіїв. Ця специфічна асиметрія зростає з наближенням i-шару до центру нанодроту. При цьому відбувається зменшення густини струму в «довгому» p-i-n-діоді та її збільшення в «короткому» (при даній прямій напрузі). А зміна радіальної товщини i-шару демонструє максимуми в густині струму при товщині, близькій до довжини біполярної дифузії.